325. THE ASSOCIATED RISK BETWEEN SINGLE NUCLEOTIDE POLYMORPHISMS OF AP1S1 AND ESOPHAGEAL SQUAMOUS CELL CARCINOMA IN CHINESE POPULATION. (24th September 2022) - Feng, Su; Yong, Fang; Jinjie, Yu; Tian, Jiang; Siyun, Lin; Shaoyuan, Zhang; Lu, Lv; Tao, Long; Huiwen, Pan; Junqing, Qi; Qiang, Zhou; Weifeng, Tang; et al.
Abstract: The σ1A subunit of the adaptor protein 1 (AP1S1) participates in intracellular transport pathways, which is pivotal in carcinogenesis. It is therefore rational to presume that AP1S1 might also be involved in carcinogenesis. In this hospital-based case–control study, we investigated the genetic susceptibility to esophageal squamous cell carcinoma (ESCC) in relation to Single Nucleotide Polymorphisms (SNPs) of AP1S1 among Chinese population and made a preparation for the subsequent esophageal SNP risk model building. A database containing a total of 1143 controls and 1043 ESCC patients were retrospectively studied. The AP1S1 SNPs were analyzed based on ligation detection reaction (LDR) method. Then the relationship between ESCC and SNPs of AP1S1 was determined with a significant crude P < 0.05. Then the logistic regression analysis was used for the calculation for adjusted P in the demographic stratification comparison if a significant difference was observed in the previous step. AP1S1 rs77387752 C > T mutated homozygous TT was an independent risk factor for ESCC, while SNP rs4729666 C > T and rs35208462 C > T mutated heterozygote TC were associated with a lower risk for ESCC, especially in co-dominant model and allelic test for younger, male subjects who are not alcohol-drinkers nor cigarette smokers. These three AP1S1 SNP sites could be incorporated into subsequent SNPs risk models for ESCC in specific populations. AP1S1 rs77387752, rs4729666 and rs35208462 polymorphisms are associated with susceptibility to ESCC in Chinese individuals. AP1S1 SNPs may exert an important role in esophageal carcinogenesis and could serve as potential diagnostic biomarkers. These SNP sites might be added into the building of risk model and then the early diagnosis of ESCC. Besides, further mechanical exploration is required. Table. Logistic regression analyses of associations between AP1S1 SNPs rs77387752 C > T, rs4729666 C > T, rs35208462 C > T and risk of ESCC.